Biological pathways and mechanisms linking COPD and cardiovascular disease - Beatrice Ragnoli; Fausto Chiazza; Giovanni Tarsi; Mario Malerba (Therapeutic Advances in Chronic Disease)
Cardiovascular disease (CVD) still poses a significant risk for morbidity and mortality in patients with chronic obstructive pulmonary disease (COPD). For a long time, among functional parameters, only the forced expiratory volume in 1 s (FEV 1 ) has been considered as predictive of cardiovascular (CV) mortality especially in elderly patients in fact, there is evidence that reductions in lung function indices can increase the risk of ischaemic heart diseases and cerebrovascular diseases, independently from other risk factors. Now, there is considerable evidence suggesting that hypoxemia, systemic inflammation, oxidative stress and hyperinflation may lead to an early sub-clinical CV involvement in patients affected by COPD. Ageing in itself impacts specific aspects of the CV system, including reduced beta-adrenergic responsiveness, increased vagal tone and myocardial and vascular stiffness, endothelial dysfunction, diminished arterial baroreflex and compromised diastolic function. The complex involved interactions include ageing mechanisms as well as multiple known and unknown (e.g. genetic) risk factors. CVDs are leading causes of mortality in individuals with impaired lung function and the two entities commonly coexist with poor outcomes in patients experiencing both conditions. However, the precise mechanisms responsible for this association remain largely unknown. In this narrative review, we summarize current knowledge regarding the co-occurrence of COPD and CVD focusing on the shared biological pathways and biological mechanisms involved in these conditions.